Pengendalian Internal, Ketaatan Aturan Akuntansi, dan Perilaku Tidak Etis Terhadap Kecenderungan Kecurangan Akuntansi - Prakoso, Muhammad Iqbal; Khairunnisa, Hera; Prihatni, Rida (LPPM Universitas Negeri Jakarta, 2023)
This study aims to determine the effect of internal control, observance of accounting rules, and unethical behavior on accounting fraud tendencies. This type of research is qualitative with primary data assisted by the Google form. The sample of this research was 86 respondents from the Bureau of Finance and State Property (BMN) at the Ministry of Education, Culture, Research and Technology. The data analysis method used is inferential statistical analysis as measured using PLS-SEM in SmartPLS 3.0 software. Based on the research results show that: 1) Internal control does not have a significant effect on the tendency of accounting fraud; 2) Compliance with accounting rules significantly has a positive influence on the performance of accounting fraud tendencies; and 3) Unethical behavior does not have a significant effect on the tendency of accounting fraud.